Penerapan Metode MOORA pada Sistem Penunjang Keputusan Seleksi Karyawan Magang Keluar Negeri (Studi Kasus: PT Hinai Daiki) - Teuku Mufizar; Ade Taopik Hidayatuloh; Nanang Suciyono; Alma Husna Hanifah (LP3M Universitas Mulia, 2021)
Abstract In an organization or company, employees as Human Resources (HR) are seen as a person's ability to do work within the company, especially when viewed from the portion to help the company achieve its goals. One form of good Human Resources (HR) management is to provide training for employees in the company in order to improve the knowledge and skills of employees. PT Hinai Daiki as a company engaged in the export garment sector in Tasikmalaya conducts training in the form of sending apprentices abroad. Problems that occur So far, the determination of prospective overseas internships at this company is not as expected, because the selection is direct without using a decision support system, causing inaccurate assessments and not on target. This study aims to apply the MOORA (Multi-Objective Optimization on the basis of Ratio Analysis) method in assisting the selection of employees who will be sent for internships abroad at PT Hinai Daiki. The MOORA method is used in the calculation process that produces output in the form of alternative employees who will be sent for internships abroad. The criteria used in this study include activeness in work, mastery of work, discipline, knowledge, teamwork, personality, mastery of language and health. Based on the research results, the MOORA method can be well applied to the decision support system for the selection of interns at PT Hinai Daiki.